Determinan Harga Saham pada Perusahaan Sektor Pertanian yang Terdaftar Di Indeks Saham Syariah (ISSI) - Mohammad Dendi Abdul Nasir (Nuris Journal of Education and Islamic Studies, 2022)
This study aims to determine the effect of fundamental factors on agricultural sector stock prices listed in the Indonesian Sharia Stock Index (ISSI). This research uses quantitative methods. Purposive sampling technique was used and taken as many as 7 companies as samples. These companies have met the criteria that provide financial reports in rupiah (Rp) and were listed in the ISSI during the 2014-2019 period. Thus, the panel data used in this study were 42 observations. Fundamental factors are proxied by ROA, ROE, and PER. The linear regression analysis is used and the results show that ROA has a significant positive effect on stock prices, ROE has a significant negative effect on stock prices, and PER does not have a significant effect on stock prices in agricultural sector companies listed in ISSI.